Day 2 Tue, May 09, 2017 2017
DOI: 10.2118/186029-ms
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Matrix Shrinkage and Stress Changes on Permeability and Gas Production of Organic-Rich Shale Reservoirs

Abstract: During reservoir depletion, effective stress is increased and permeability is reduced, while the organic- rich matrix might experience a shrinkage process that will boost the permeability. The main objective was to develop a mathematical simulator coupling gas flow process, geomechanics effects, and matrix shrinkage in order to evaluate their influences on reservoir permeability and production performance. The mesh was divided into three different continuums: organic matter, inorganic matter, and natural fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Shale nanopore size is influenced by combined effects of matrix shrinkage and stress sensitivity [32][33][34][35][36][37]. Thus, apparent permeability and gas multiple flow mechanisms are dynamically changing along with gas production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shale nanopore size is influenced by combined effects of matrix shrinkage and stress sensitivity [32][33][34][35][36][37]. Thus, apparent permeability and gas multiple flow mechanisms are dynamically changing along with gas production.…”
Section: Introductionmentioning
confidence: 99%
“…The adsorbed gas desorbs from nanopore surfaces leading matrix shrinkage and resulting in an increase in the pore size and apparent permeability [32][33][34]. In contrast, the effective stress of the matrix skeleton increases as gas in nanopores flow out, causing the pore to be compressed [35,36]. Dong [35] and Mckee's [37] research results have shown that a decline in permeability has a negative exponential relationship with the effective stress.…”
Section: Introductionmentioning
confidence: 99%
“…More details will be discussed later in the text. Although there are many existing numerical models for shale gas simulation, many of the above complex phenomenon have not been completely captured, and hence it is necessary to develop a powerful model to fill this gap in the petroleum industry.…”
Section: Introductionmentioning
confidence: 99%
“…The stress sensitive permeability was incorporated in their model using a lab-validated correlation. An et al used a coupled flow and geomechanics simulator to test the effect of stress-dependent permeability on hydrocarbon production in organic-rich shale reservoirs [19]. They indicated that the selection of the correlation for the stress-dependent permeability significantly affects the field production performance.…”
Section: Introductionmentioning
confidence: 99%
“…While these researches provide insights in numerical investigations of stress sensitive reservoir rocks, limitations of these previous numerical studies are observed. In An et al [19] and Shovkun and Espinoza [20], the numerical methods for the geomechanics modeling only consider linear elasticity, implying that these numerical methods could not describe the nonlinear elastic behaviors as rocks are being compacted and consolidated due to in-situ stresses changes and hydrocarbon depletion in the reservoir. The correlations between rock deformation and stress sensitive rock properties were theoretically derived and they lack the validation with field/experimental results, indicating that their methods work for theoretical analysis but have limitations when it comes to realistic shale rocks [19,20].…”
Section: Introductionmentioning
confidence: 99%